Sukuk and Nation Building: An Overview of the Development and Impact of Sukuk Financing in Nigeria - Abu Bakar, Adam; Muhammad Baba, Ibrahim (Universitas Islam Negeri Raden Intan Lampung, 2020)
AbstractAccording to Islamic Financial Service Board (IFSB), Sukuk are certificates that represent the holders’ proportionate ownership in an undivided part of underlying asset where the holder assumes all right and obligations to such asset. The emergence of Sukuk in Islamic capital markets is a significant development that provides alternative funding avenue for corporate entities, government and financial institutions. Despite the tremendous growth of Sukuk finance globally, the phenomenon is relatively new in Nigeria, though the regulator, Securities and Exchange Commission (SEC) has issued guidelines for the operation and placing of Sukuk in the country, apart from Osun State Government that has listed its Sukuk and the recent FGN Sukuk issuance, evidence shows that, none within the corporate and financial bodies had listed any Sukuk in Nigeria. It is against this backdrop that this paper aims at assessing the role of Sukuk financing in nation building with special reference to the recent Sukuk issuance by the Federal Government for the rehabilitation of Federal roads across the six geo-political zones of the Country. The researchers adopted analytical and descriptive approaches in this study. The main findings of the paper have shown that despite the novelty of Sukuk finance to Nigerian context, it has incalculable impact on nation building. It also revealed that Ṣukūk have many economic benefits and potentialities to Nigerian economy in terms of economic growth, financial inclusion, diversification, Liquidity Control and infrastructural financing, among others.